Job flows, demographics and the Great Recession - Eva Sierminska; Yelena Takhtamanova (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The recession the United States economy entered in December of 2007 is considered to be the most severe downturn the country has experienced since the Great Depression. The unemployment rate reached as high as 10.1 percent in October 2009 - the highest we have seen since the 1982 recession. In this paper we examine the severity of this recession compared to those in the past by examining worker flows into and out of unemployment taking into account changes in the demographic structure of the population. We identify the most vulnerable groups of this recession by dissagregating the workforce by age, gender and race. We find that adjusting for the aging of the U.S. labor force increases the severity of this recession. Our results indicate that the increase in the unemployment rate is driven to a larger extent by the lack of hiring (low outflows), but flows into unemployment are still important for understanding unemployment rate dynamics (they are not as acyclical as some literature suggests) and differences in unemployment rates across demographic groups. We find that this is indeed a mancession, as men face higher job separation probabilities, lower job finding probabilities and, as a result, higher unemployment rates than women. Lastly, there is some evidence that blacks suffered more than whites (again, this difference is particularly pronounced for men).
Keywords: J1; J6; 330; Unemployment; Worker flows; Job Finding Rate; Separation Rate; Demographics; Gender; Arbeitslosigkeit; Arbeitsmobilität; Arbeitsuche; Alternde Bevölkerung; Geschlecht; Konjunktur; Wirtschaftskrise; USA